Test of CP invariance in higgs boson vector-boson-fusion production using the H → γ γ channel with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physical review letters, 2023)
A test of 𝐶⁢𝑃 invariance in Higgs boson production via vector-boson fusion has been performed in the 𝐻 →𝛾⁢𝛾 channel using 139  fb−1 of proton-proton collision data at √𝑠 =13  TeV collected by the ATLAS detector at the LHC. The optimal observable method is used to probe the 𝐶⁢𝑃 structure of interactions between the Higgs boson and electroweak gauge bosons, as described by an effective field theory. No sign of 𝐶⁢𝑃 violation is observed in the data. Constraints are set on the parameters describing the strength of the 𝐶⁢𝑃-odd component in the coupling between the Higgs boson and the electroweak gauge bosons in two effective field theory bases: ˜𝑑 in the HISZ basis and 𝑐𝐻⁡ ˜ 𝑊 in the Warsaw basis. The results presented are the most stringent constraints on 𝐶⁢𝑃 violation in the coupling between Higgs and weak bosons. The 95% C.L. constraint on ˜𝑑 is derived for the first time and the 95% C.L. constraint on 𝑐𝐻⁡ ˜𝑊 has been improved by a factor of 5 compared to the previous measurement.
Veröffentlicht: 7. August 2023
*ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2908 weitere Personen]
Gesehen am 03.07.2025